ARIMA Method Implementation for Prediction of Oyster Mushroom Production - Nita Syahputri; Ommi Alfina; Labuan Nababan; Ulfah Indriani (IJISTECH (International Journal of Information System and Technology), 2022)
Ad-Dhuha Farm is an MSME (Micro, Small and Medium Enterprises) business engaged in the production of oyster mushrooms. In producing oyster mushrooms for sale, Ad-Dhuha usually estimates based on production logbooks. So that sometimes the results of predictions that are made miss estimates, this is because there is no proper calculation based on the data used so that there is a buildup of oyster mushroom supplies. This affects the progress of MSME businesses (Micro Small and Medium Enterprises) because seeing from the need to pay workers, invoices for operational needs and so on so that MSME businesses (Micro Small and Medium Enterprises) suffer losses. This study uses the ARIMA method to predict the amount of oyster mushroom production in Ad-Dhuha. With the ARIMA method, Ad-Dhuha can predict the amount of production so that there is no accumulation of oyster mushrooms.